2016
DOI: 10.1097/md.0000000000004506
|View full text |Cite
|
Sign up to set email alerts
|

Nurse prescribing in Poland

Abstract: The aim of this study was to identify and examine the differences in opinions held by health care professionals and the general public concerning the right to administer and prescribe medication which has been awarded to nurses and midwives in Poland.The study was conducted from December 1, 2014 to July 1, 2015, in randomly selected primary health care clinics, among 2227 individuals, including 849 subjects representing medical personnel of primary health care and 1378 patients receiving primary care services.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…These issues justify the difference between their findings and the results of this study regarding nurses' readiness for prescribing [13]. In another study conducted by Binkowska-Bury et al, more than half of nurses were not ready to take responsibility for prescribing [16]. The finding of this study is not consistent with their findings, probably due to the educational attainment of participants.…”
Section: Discussioncontrasting
confidence: 95%
“…These issues justify the difference between their findings and the results of this study regarding nurses' readiness for prescribing [13]. In another study conducted by Binkowska-Bury et al, more than half of nurses were not ready to take responsibility for prescribing [16]. The finding of this study is not consistent with their findings, probably due to the educational attainment of participants.…”
Section: Discussioncontrasting
confidence: 95%
“…Another study at primary health care facilities regarding the nurses' opinion on writing prescriptions showed that the vast majority pointed to medical devices, followed by medicines previously ordered by a doctor and foodstuffs for particular nutritional uses [41]. A similar position on the subject of prescribing medicines by nurses was expressed in another study by doctors [42].…”
Section: Discussionmentioning
confidence: 74%
“…To date, there have not been any other analyses of nurse prescribing in Poland during the implementing period. Some Polish research has reported the positive opinions of nurses about prescribing [20][21][22], but that research did not assess nurse prescribing practice. A better understanding of the determinants of prescribing patterns in Poland may help shape future workforce policy in the medical sector and contribute to the design and implementation of optimal and cost-effective initiatives to improve care quality.…”
Section: Discussionmentioning
confidence: 99%